Determinants factors on Public Health Centre nurses' confidence in performing cardiopulmonary resuscitation - Priyo Sasmito; Elly Purnamasari; Sri Sumartini; Nunuk Sri Purwanti; Budiyati Budiyati; Riskiyana Sukandhi Putra; Nisa Arifani; Yeni Elviani (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2024)
Background: Most cardiac arrests occur outside the hospital (out-of-hospital cardiac arrest/OHCA). Public Health Centre (PHC) nurses are one of the important components of the chain of survival. The confidence of PHC nurses in performing Cardiopulmonary resuscitation (CPR) is still questioned.Purpose: To analyze the factors determining the level of confidence of PHC nurses in performing CPR.Method: An observational analytical study with a cross-sectional approach involving 30 nurses from 2 PHCs in Banten Province, Indonesia taken using a total sampling technique.Results: A total of 30 participants participated in this study. The average age of participants was 36.4 years with an age range between 26-55 years. Most participants were male 17/56.7%, had a diploma education background of 21/70.0%, and had upgraded their BLS training 23/76.7%. On average, participants had worked for 6.5 years and managed 3.4 cases of cardiac arrest (CA) during their time as nurses. It was found that gender, educational background, and BLS training status were not associated with the nurse's level of confidence in performing CPR. While employment status has a significant relationship with confidence in performing. Age has a strong relationship with self-confidence with an r rank value of 0.447. Length of work also showed a relationship with self-confidence with an r-rank value of 0.503. Likewise, the number of CA cases ever managed has a relationship with self-confidence with an r rank of 0.419.Conclusion: Gender, educational background, and BLS training status were not associated with nurses' confidence levels in performing CPR. Employment status, age, length of work, and number of CA cases managed were associated with nurses' confidence in performing CPR.